Tissue-Associated Bacterial Alterations in Rectal Carcinoma Patients Revealed by 16S rRNA Community Profiling - Thomas, Andrew M.; Jesus, Eliane C.; Lopes, Ademar; Aguiar, Samuel; Begnami, Maria D.; Rocha, Rafael M.; Carpinetti, Paola Avelar; Camargo, Anamaria A.; Hoffmann, Christian; Freitas, Helano C.; Silva, Israel T.; Nunes, Diana N.; et al. (Frontiers in Cellular and Infection Microbiology, 2016)
Sporadic and inflammatory forms of colorectal cancer (CRC) account for more than 80% of cases. Recent publications have shown mechanistic evidence for the involvement of gut bacteria in the development of both CRC-forms. Whereas colon and rectal cancer have been routinely studied together as CRC, increasing evidence show these to be distinct diseases. Also, the common use of fecal samples to study microbial communities may reflect disease state but possibly not the tumor microenvironment. We performed this study to evaluate differences in bacterial communities found in tissue samples of 18 rectal-cancer subjects when compared to 18 non-cancer controls. Samples were collected during exploratory colonoscopy (non-cancer group) or during surgery for tumor excision (rectal-cancer group). High throughput 16S rRNA amplicon sequencing of the V4-V5 region was conducted on the Ion PGM platform, reads were filtered using Qiime and clustered using UPARSE. We observed significant increases in species richness and diversity in rectal cancer samples, evidenced by the total number of OTUs and the Shannon and Simpson indexes. Enterotyping analysis divided our cohort into two groups, with the majority of rectal cancer samples clustering into one enterotype, characterized by a greater abundance of Bacteroides and Dorea. At the phylum level, rectal-cancer samples had increased abundance of candidate phylum OD1 (also known as Parcubacteria) whilst non-cancer samples had increased abundance of Planctomycetes. At the genera level, rectal-cancer samples had higher abundances of Bacteroides, Phascolarctobacterium, Parabacteroides, Desulfovibrio and Odoribacter whereas non-cancer samples had higher abundances of Pseudomonas, Escherichia, Acinetobacter, Lactobacillus and Bacillus. Two Bacteroides fragilis OTUs were more abundant among rectal-cancer patients seen through 16S rRNA amplicon sequencing, whose presence was confirmed by immunohistochemistry and enrichment verified by digital droplet PCR. Our findings point to increased bacterial richness and diversity in rectal cancer, along with several differences in microbial community composition. Our work is the first to present evidence for a possible role of bacteria such as Bacteroides fragilis and the phylum Parcubacteria in rectal cancer, emphasizing the need to study tissue-associated bacteria and specific regions of the gastrointestinal tract in order to better understand the possible links between the microbiota and rectal cancer.